Transcranial Electrical Stimulation (TES) as a Possible Novel Alternative to Transcranial Magnetic Stimulation (TMS) to Assess the Motor Function of the Spinal Cord for Clinical Diagnosis in Horses. (September 2014) - Journée, S.L.; Delesalle, C.J.G.; de Bruijn, C.M.; Bergmann, W.; Journée, H.L.
Abstract : Reasons for performing study: To introduce and assess the feasibility of multipulse transcranial electrical stimulation (TES) in horses. Objectives: To assess latency times of muscular motor evoked potentials (MEP) in the m. extensor carpi radialis (ECR) and the m. tibialis cranialis (TC), elicited by transcranially applied multipulse stimulation in 12 healthy horses. Study design: Prospective observational study applied in 12 healthy horses. Methods: Horses with a mean age of 11.0 (range 3.6–20.5) years and a height of 160 (s.d. ± 10.0) cm were studied. Horses were sedated with detomidin (1.5 μg/kg bwt) and butorphanol (1.5 μg/kg bwt) i.v. A subcutaneous ring block with lidocaine 2% + adrenaline was placed on the forehead. TES was performed using biphasic high frequency multipulse voltage trains (pulse width: 0.1 ms, interpulse interval: 1.3 ms, 3 pulses/train) applied to 2 subcutaneous needle electrodes bilateral from the centre of the forehead. Latency times (30 V above motor threshold (MT) and amplitude of MEP were recorded bilaterally at the ECR and the TC muscles. Motor latency times are expressed as mean ± 2 s.d. Results: Mean latency times (at MT + 30 V) for the ECR muscles were respectively 20.18 ± 1.85 ms (left side) and 19.7 ± 1.69 ms (right side) and for the TC muscles respectively: 34.6 ± 2.01 ms (left) and 34.9 ± 2.43 ms (right). Conclusions: TES is well tolerated. Interestingly, recorded motor latency times at the level of front and hind legs appear to be shorter for TES when compared to TMS from literature data [1]. Ethical animal research:  Ethical approval was granted by the animal ethics committee of the Groningen University.Sources of funding:  JS Center and Wolvega Equine Clinic.Competing interests:  None.